South Cuidrach: a new Late Upper Palaeolithic and Mesolithic site on the Isle of Skye, western Scotland - Hardy, Karen; Ballin, Torben (Proceedings of the Society of Antiquaries of Scotland, 2024)
A new site in north Skye has revealed evidence of human occupation from the Late Upper Palaeolithic as well as the Early and Late Mesolithic periods, suggesting repeated visits by humans for at least 5,000 years from the Late Glacial Interstadial through the Loch Lomond Readvance and up to the mid-Holocene, a time of dynamic climatic and sea-level change. South Cuidrach is one of several sites in the north of the Isle of Skye and around the Inner Sound with lithic (stone tool) evidence diagnostic of a human presence before the mid-Holocene. These sites currently represent a unique concentration of pre-Late Mesolithic sites in Scotland. The lithic evidence which forms the backbone of the cultural and temporal characterisation of the site at South Cuidrach is outlined here. This includes characteristic points and microliths, burins, cores and other items diagnostic of specific cultural groups. Additionally, it has become evident that Rum bloodstone, a raw material well known from the Late Mesolithic period in the region, may be absent before the Early/Late Mesolithic transition, with baked mudstone from Staffin in North Skye being the primary raw material used before this time. The need for detailed knowledge of the region’s lithic technology and typology is well illustrated here, as small details frequently reflect important chronological differences.